Interpretation of Mutasyabihat Verses (A comparative study of the meanings of Istawa and Yad in Tafsir Fathul Qadir and Tafsir Al-Misbah) - Hilmie, Muhammad; Rhain, Ainur (Universitas Muhammadiyah Surakarta, 2023)
The interpretation of the verse mutasyabihat in the Qur'an is a complex problem in Islamic studies. These verses have meanings that seem ambiguous or open to various interpretations. The interpretation of the Qur'an can vary greatly depending on the context. Some differences can arise in literal versus figurative (distorted understanding), historical context, as well as philosophical or theological approaches in interpreting this sacred text. Especially in interpreting the verse mutasyabihat related to the nature of Allah which will be the focus of our discussion in this writing. The problem is, there are still many people who make an understanding of the similarity of the nature of Allah جل جلاله with the nature of beings (Tashbih). For example, the assumption that Allah sits on 'arsh. Or in other words, God needs his creatures. This kind of understanding is a wrong understanding. It can even affect the understanding of Muslim society, then affect our faith as Muslims. In fact, we know that equating Allah with his legal beings is Haram. So this study tries to explore the interpretation of two mufassir figures, namely, Imam ash-Syaukhani and Quraish Shihab. Especially the interpretation of mutasyabihat verses related to the nature of Allah. Based on the previous description, there are several focus studies in this study : 1) What is the interpretation of Imam ash-Shaukhani and Quraish Shihab on the meaning of istiwa in sura al-A'raf verse 54. 2) How the interpretation of Imam As Syaukani and Quraish Shihab is the meaning of yad in the sad letter : 75. In this study we used qualitative research with literature method. The results of this study explain that, both have differences in interpreting the meaning of istiwa and yad. And each uses a different method of interpretation. 1) Imam Shaukhani argues that Allah dwells in no way. While Quraish Shihab thinks that the meaning of istawa is the power of Allah. 2) Imam Shaukhani interpreted the meaning of yad to mean